Evaluation of the anti-Thomsen-Friedenreich antibodies Nemod-TF1 and Nemod-TF2 as prognostic markers in breast cancer - Heublein, Sabine; Egger, Markus; Zhu, Junyan; Berger, Luisa; Mayr, Doris; Schindlbeck, Christian; Kuhn, Christina; Hofmann, Simone S.; Schütz, Florian; Jeschke, Udo; Ditsch, Nina (Breast cancer research and treatment, 2020)
The TF (Thomsen-Friedenreich, CD176, Galβ1-3GalNAc) carbohydrate moiety is known as a specific oncofetal carbohydrate epitope present in fetal and neoplastic tissue as well as in stem cells. TF was demonstrated to mediate tumor-promoting features and to be highly immunogenic. The current study aimed to evaluate whether presence of the TF antigen is associated with clinico-pathological parameters and prognosis of early breast cancer (BC).
Published online: 11 December 2019
Gesehen am 02.04.2020